Effect of de Carbon/Nitrogen ratio on the production of microalgae-based carotenoids (2020)
This study investigates the effect of C/N ratio on the production of biomass and total carotenoids on a Scenedesmus sp. Initially, three different carbon sources (sodium carbonate, sodium bicarbonate and sodium acetate) were tested under different concentrations of a nitrogen source (sodium nitrate) in 250 mL tubular air-lift reactors. The reactors were operated at 25 °C for 40 days. in light:dark cycle of 12:12, under a continuous flow of air. Results showed that by the adjustment of the concentration of the carbon and nitrogen source, it is possible to increase the concentration of biomass up to 0.8 g/L. However, by the regulation on the concentration of sodium carbonate and sodium nitrate, the final content of total carotenoids was increased two times (from 0.3 to 0.66 % w/w). Results from this study shows that an specific ratio between the carbon source employed and the concentration of the nitrogen source shows that an outstanding increase on the final biomass and the concentration of total carotenoids that can be produced. Finally, the effect of well-known strategies such as light, salinity and pH, coupled with C/N ratio must be studied to achieve a proper method to stress the cell culture and enhance the synthesis of carotenoids in Scenedesmus sp.